China–Africa Education Cooperation: From FOCAC to Belt and Road. (June 2020) - King, Kenneth
Purpose: The article discusses the relationship between the human resource traditions of the Forum on China–Africa Cooperation (FOCAC) and those supported by the Belt and Road Initiative (BRI), and in particular by the Education Action Plan for the Belt and Road Initiative, issued by the Chinese Ministry of Education (MOE) in 2016. Design/Approach/Methods: The article draws upon discourse analysis of both the FOCAC VI and VII documents and the key MOE 2016 Action Plan. Findings: Given the trans-continental coverage of the BRI, it is suggested that its ambitious pledges in respect of education and human resource development (HRD) actually complement or even exceed the commitments made by FOCAC VI and VII. Originality/Value: This is the first article explicitly to compare the HRD pledges of FOCAC with those associated with BRI's Education Action Plan.